TAXATION ON DIVIDENDS AND ITS IMPACT ON COMPANIES IN THE ELECTRICITY SECTOR IN BRAZIL, THE UNITED STATES AND GERMANY - Rodrigues da Silva, Alexandre (Revista UNEMAT de Contabilidade, 2024)
The objective of this work is to analyze, through the payment of dividends from companies in the electricity sector in Brazil, the United States and Germany, the possible influence of their respective tax legislation on dividend policy and also on the price of assets. Methodology: data on dividend payments and daily value of shares of companies in the electricity sector in Brazil, the United States and Germany, respectively traded on the São Paulo, New York and Frankfurt stock exchanges, were collected. The period was covered from January 1, 2000 to December 31, 2022. Results: Brazilian companies in the electricity sector pay more dividends than companies in the same sector listed on the New York and Frankfurt stock exchanges. The share price is negatively influenced by dividends in companies in the United States and Germany, but there was no correlation between changes in asset prices and dividend payments in the case of Brazil.